Morbidity and Mortality of ICD: migraines and other cephalic pain syndromes, by age group and gender in brazilian regions - Cezar, Vitória Luisa Batista; Souza, Marcelo Alves de (Headache Medicine, 2024)
Introduction: Headaches are the third most common complaint in outpatient services, with a prevalence of 10.3%, second only to respiratory tract infections and dyspepsia. Understanding hospitalizations and deaths related to headaches is essential for studying their etiology, treatment, and prevention. Objective: Analyze hospitalization and death rates due to headaches in different Brazilian regions from 2019-2023, providing epidemiological data to aid in developing strategies to combat the disease. Methods: Longitudinal observational epidemiological study covering Brazil’s demographic regions from 2019-2023. Data were sourced from the SUS Informatics Department (DATASUS) and the Hospital Information System (SIH/SUS) based on hospitalizations and deaths recorded by ICD-10 (G43; G43.0; G43.1; G43.8), considering sex and age variables. Results: Migraines and similar conditions, despite high outpatient demand, accounted for only 0.086% of hospitalizations over the past five years. The Southeast and Northeast showed stable rates between 2019-2023 (<0.01 amplitude), while the South and Center-West exhibited greater fluctuations (>0.01). The North recorded a continuous increase in hospitalizations (from 0.0601% to 0.1081%), reflecting higher disease rates requiring hospitalization. Specific ICD mortality rate for hospitalizations in Brazil was 0.95%, with the North region showing a higher average (around 2.87%). The Northeast showed a gradual increase (1.07%-2.30%), while other regions remained below 0.7%, indicating possible variations in regional health policies, medical infrastructure, and disease prevalence. The were a female predominance in hospitalizations, with regional averages from 2.20 (Southeast) to 1.82 (North). The highest hospitalization rates were among the age groups 20-29 and 30-39 years (1739,6; 1860,2 national means respectively), decreasing gradually after age 40 (1730,2) onwards, which menopause and work-related stress may have influenced. Hospitalizations for children and adolescents were higher in the Northeast, Southeast, and South (regional means: 330,4; 339,4 339,4) regions compared to North and Center-West (62,2; 64). Conclusion: During the analyzed period hospitalization and death rates due to headaches in Brazil remained a stable overall. Data showed significant variations concerning region, gender and age, indicating the need to consider regional and demographic differences in developing public health plans and policies to minimize public spending and reduce patient suffering.